Analisis Pastoral Holistik Kedukaan dalam Kitab Ayub 1:13-22 dan Relevansinya pada Tradisi "Malam Penghiburan" di Gereja Lokal: Berdasarkan Teori Elisabeth Kübler Ross - Apitalau, Erica; Larissa, Triana Queen Aurelya; Janis, Vinkan Anggita (DELAHA: Journal of Theological Sciences, 2025)
This article offers an analytical study related to Holistic Grief Pastoral Care contained in the book of Job 1:13-22 regarding the story of Job who lost his property in the form of animals and children he loved in a short time, thus making Job feel devastated. The author compares the story with the local church's response in providing holistic grief pastoral care through the tradition of "Night of Consolation." This research identifies five stages related to each individual or group in responding to openness, according to the theory of Elisabeth Kϋbler Ross. The results showed that the importance of the church's role in providing Pastoral Care or grief pastoral guidance well. This research shows that the story of Job contains a deep meaning related to his grief after experiencing loss and this can also be a reference for the church in responding to the suffering of the congregation who feel the impact of grief.